2012
DOI: 10.1103/physrevb.86.085141
|View full text |Cite
|
Sign up to set email alerts
|

Orbital states of V trimers in BaV10O15detected by resonant x-ray scattering

Abstract: BaV 10 O 15 shows a structural phase transition associated with the trimerization of V ions at T s = 123 K. We investigated the orbital states of V trimers using the technique of resonant x-ray scattering (RXS) near the V K-edge absorption energy. The ratio of the intensity between the pre-edge structure (1s to 3d transition) and the main-edge structure (1s to 4p transition) strongly depends on the reciprocal Q position of the scattering. We found that the Q position dependence is consistent with the model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Below T tr , the lone V ion at the center forms a V trimer with two V ions of the surrounding two tetramers, and the two tetramers are accordingly changed into two trimers; thus 13 V ions are separated into three trimers and one remaining tetramer. Note that such a trimerization of V ions at low T was observed in various vanadates in which V 3+ (3d 2 ) ions form a quasi-fcc lattice [5,6] and was attributed to the orbital ordering of V t 2g states [7]. The resistivity and magnetic susceptibility of SrV 13 O 18 decrease at T tr .…”
mentioning
confidence: 78%
“…Below T tr , the lone V ion at the center forms a V trimer with two V ions of the surrounding two tetramers, and the two tetramers are accordingly changed into two trimers; thus 13 V ions are separated into three trimers and one remaining tetramer. Note that such a trimerization of V ions at low T was observed in various vanadates in which V 3+ (3d 2 ) ions form a quasi-fcc lattice [5,6] and was attributed to the orbital ordering of V t 2g states [7]. The resistivity and magnetic susceptibility of SrV 13 O 18 decrease at T tr .…”
mentioning
confidence: 78%
“…Another example is LiVO 2 with triangular lattice in which the two t 2g electrons per V site form single bonds in two different directions and help trimerization of three V sites [6][7][8]. The trimerization and the face sharing bond coexist in BaV 10 O 15 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In the LiVO 2 , trimerization below ∼ 550 K is observed with the orbital induced structural transition and the formation of spin singlets of the triangular lattice. [8][9][10] The BaV 10 O 15 undergoes a structural transition accompanied by V trimerization and V 3d orbital order at 120 K. 11,12 Recently, the insulating phase below 120 K in BaV 10 O 15 is reported with V 2+ -V 3+ charge ordering whereas the metallic phase at 300 K with V 2.5+ -V 2.5+ bond ordering by Yoshino et al 13 The BaV 10 O 15 unit cell contains five VO 6 octahedra as a boat sharing the edge or face of the octahedron at each of its four layers. The first layer shares the face with the fourth layer and shares the edge with the second layer where the V trimerization occurs between adjacent layers below 120 K. The V 2+ and V 3+ arrangements at the low temperature (75 K) in BaV 10 O 15 provide V 3d orbital ordering analogous to that known in the triangular lattice in LiV 3+ O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The Raman studies previously reported on the presence of randomly oriented trimers with decreasing temperature below 220 K. 16 In addition, the splitting of V nuclear magnetic resonance (NMR) spectra indicated the symmetry lowering and no structural transition below 220 K. 17 Further from the NMR and X-ray diffraction measurements, the phase diagram of BaV 10 O 15 has shown the high-temperature phase (300 K -220 K), the intermediate-temperature phase (220 K -130 K), and the low-temperature phase (below 130 K). 17 Although the structural, transport, and optical properties are studied for BaV 10 O 15 including the electronic properties only at 75 and 300 K, [11][12][13] the electronic properties across the intermediate-temperature phase have not yet been studied. In view of the complicated transport and optical properties across the intermediate-temperature phase, 11,16,17 the present work is dedicated to study the electronic properties at 180, 245, and 300 K including the insulating phase (70 K).…”
Section: Introductionmentioning
confidence: 99%